An ecological study of the grasslands of the jack scott nature reserver, transvaal, with special reference to plant production and ungulate-habitat relationships - Theron, G.K. (University of Pretoria, 2022)
Dissertation (MSc (Wildlife Management))--University of Pretoria, 1988.